Gender Approach in the Study of Islamic Law - Kabalmay, Fakhrurrozi (Edumaspul: Jurnal Pendidikan, 2024)
Gender is a global issue that is constantly discussed and, it would seem, endlessly, equality is desired in the economy, politics, social, household, etc. spheres. Gender is the difference between men and women that is formed in social life through roles, behaviors and characters that are considered worthy of exchange between men and women. Gender issues have been increasingly discussed over the centuries, as many issues of inequality are still discussed, including Injustice, stereotypes, subordination, impoverishment of women, marginalization, violence, negative labeling, exploitation and free trade., which women often face. In Islam, gender is also an interesting topic for discussion by scholars based on the main source of Islamic law, the Qur’an, and contains many different opinions. The purpose of this article is to consider the gender approach in the study of Islamic law. The method used in the article is a qualitative research method with a library approach, which uses links to books, journals and other scientific works. According to the results of the study, Islam strongly opposes the existence of gender inequality that women often face, since the position of men and women in the Qur’an is considered equal, among other things, both as servants and in the fact that they are potentially ideal servants., fulfilling the obligations of the leaders (caliphs), Adam and Eve were equally involved in the cosmic drama, and equally accepted the original covenant. if viewed from the point of view of equality between men and women, then women should be given rights and freedoms in the field of education, politics and other everyday issues as long as they have the ability in this area, but do not overdo it.in order not to violate their feminine nature.